SEDENTARISM, ACADEMIC BURNOUT, AND MOTIVATION OF UNIVERSITY STUDENTS; IN PRACTICE OF ONLINE LEARNING DURING COVID CONDITION - Sheeba Shahzadi; Dr. Afshi Yahya Khan; Dr. Muhammad Badar Habib; Fizza Chaudhary; Afifa (International Journal of Contemporary Issues in Social Sciences, 2024)
The present study was aimed to explore the relationship between Sedentarism, academic burnout, and motivation of university students on online learning during Covid condition. Prior to data collection pilot study was conducted on 20 participants for use in the main study. To address the main purposes of the study, we then employed a quantitative, cross-sectional research design, with a sample of 405 undergraduate male and female students aged between 18 - 24 years (M=21.9; SD=1.38) taken from various public and private sector universities of upper Punjab. The participants completed the International Physical Activity Questionnaire (IPAQ), the Burnout Scale for University Students, and Academic Motivation Scale along with the demographic sheet. Statistical analysis includes Pearson correlation, multiple hierarchal regression, independent sample t-test, and ANOVA to evaluate the correlation, prediction, and differences among variables. The results revealed a significant positive correlation was found between sedentarism and academic burnout and a significant negative correlation between academic burnout and motivation. The regression coefficient revealed the gender, sedentarism, and burnout factors including emotional exhaustion and boredom as significant negative predictors of motivation. The findings can be utilized to create awareness and devise an intervention plan for students to prevent the long-lasting detrimental impact of a sedentary lifestyle.